Розрахунки кисневого режиму при біологічній доочистці стічних вод фільтруванням - Маслун, Г.С. (Екологічна безпека та природокористування, 2012)
The method of calculating of the parameters of the biological purification of the waste waters on the filters on the base of the developed general mathematical model which taking into account the oxygen regime is proposed. The features of the posttreatment by the filtering consist in the formation the surface of the load of the biofilm with the high concentration of the microorganisms which requires the oxygen for its growth and activity. The different technologies of the supply of the oxygen and the consumption features are taken into account.